Emotion Regulation And Psychotherapy: Adaptation And Elaboration Of An Application Manual Of The Observer Measure Of Affect Regulation (O-Mar) - Almeida, Catarina; Silva, Diogo; Nogueira, Daniela; Fernandes, Cristiana; de Jesus, Saul Neves; Salgado, João (Journal of Tourism, Sustainability and Well-being, 2016)
The aim of this work was to adapt and develop a Portuguese manual for the Observer Measure of Affect Regulation (O-MAR; Watson & Prosser, 2006), an observational measure of clients’ emotion regulation in psychotherapy. Since the scale has not yet been adapted to Portuguese, initially a translation was performed. Then, to elaborate the manual, the middle 20 minutes of 20 therapy sessions were observed and classified and 2 illustrative excerpts were selected by consensus for each level of analysis of the various domains of the scale. All these videotaped sessions were collected in a randomized clinical trial carried out in Portugal for the treatment of depression, comparing 2 empirically supported models for the treatment of this disorder – cognitive behavioral therapy and emotion-focused therapy. All the participants were initially evaluated and diagnosed with mild or moderate major depressive disorder, and they attended 16 sessions of psychotherapy.